Magnetic resonance elastography increases usefulness and safety of non‐invasive screening for esophageal varices. Issue 12 (2nd July 2018) - Matsui, Nobuaki; Imajo, Kento; Yoneda, Masato; Kessoku, Takaomi; Honda, Yasushi; Ogawa, Yuji; Tomeno, Wataru; Fujisawa, Nobutaka; Misumi, Toshihiro; Kazumi, Kubota; Saito, Satoru; Nakajima, Atsushi
Abstract: Background and Aims: The Baveno VI criteria enable non‐invasive screening for esophageal varices. However, these criteria were established based on studies examining a large proportion of patients with viral hepatitis and relatively few patients with non‐alcoholic fatty liver disease (NAFLD). Furthermore, because vibration‐controlled transient elastography (VCTE) has a high incidence of measurement error, improved criteria are needed. We aimed to develop criteria based on magnetic resonance elastography (MRE) even among patients with NAFLD. Methods: We performed a cross‐sectional analysis of patients who had undergone MRE and/or VCTE as well as an esophagogastroduodenoscopy. The patients were classified as having either a low risk or a high risk of varices. The optimal cut‐offs for ruling out esophageal varices were calculated for the MRE and VCTE liver stiffness measurement (LSM), the platelet count in an estimation cohort, and the cut‐offs were then evaluated using validation cohorts composed of patients who had undergone only MRE or VCTE. Results: The study included 627 patients (39% with NAFLD). The optimal cut‐off values for the MRE‐LSM and the platelet count were 4.2 kPa and 18.0 × 10 4 /μL, respectively. An MRE‐LSM of 4.2 kPa plus a platelet count of 18.0 × 10 4 /μL had a negative predictive value of 1.00 for both low‐risk plus high‐risk varices as well as for high‐risk varices in a validation cohort, enabling the presence of varices to be ruled out. Conclusions: Magnetic resonance elastography might enable a safer avoidance of screening endoscopy, with a smaller measurement error, among patient populations with a high prevalence of NAFLD.